Understanding the Failure of the Arab Maghreb Union: A Critical Constructivits Account - Dursun, Hatice Rumeysa (Journal of History Culture and Art Research, 2021)
The Arab Maghreb Union (AMU), which was established by the countries of the region known as North Africa, also called as the Maghreb, to strengthen regional cooperation, draws attention as an organization that has lost its effectiveness today. This study examines the factors that affect the "failure" of the AMU. The discussions for the AMU to gain an active structure, which was established with the participation of Morocco, Tunisia, Algeria, Mauritania and Libya in the late 1980s, have increased even more with the current political crisis in Libya. The idea of "a united Maghreb" was actually a political argument used to mobilize the people of the region against the colonial powers during their struggle for independence long before the establishment of the AMU. Many reasons can be put forward to explain why the leaders of the region, who used the idea of creating a "united Maghreb" in their discourses, did not show enough will to achieve this dream. This study uses a critical constructivist account of state identity and interest and argues that Maghreb states were not able to develop shared identities and interests. It argues that the creation of the AMU could not pave the way for regional cooperation because Maghreb states consider each other as rivals and articulated their interests on this conception.